Human Rights in an Autonomous Political Regime. The Case of the Azores in the Context of the Covid-19 Pandemic (De Legibus - Law Journal, 2022)
The right to freedom is a fundamental human right. It is not absolute, as it admits well-founded exceptions and its essentiality is guaranteed, and with its own process and acts and the intervention of all sovereign bodies, including the courts. Such exceptional power does not belong to the autonomous regions, nor to the parliamentary legislative body, nor to the governing body that has a normative power to regulate the laws. The government of the Azores, in the Covid-19 pandemic, created rules in 2000 that limited freedom of movement, ordering to imprison in hotels any passenger entering the region, violating the Constitution and its Political Statute. It constitutes an usurpation of sovereign powers, violates the constitutional principles of separation of powers, the constitutionality of norms, and the prohibition of creating categories of normative acts not provided for in the Constitution, and the statutory principle of the Region, the realization of fundamental rights. And this political measure is dangerous: it is that the Region has its own mechanisms to obtain the results it intended in collaboration with the State: either with a “regional state of emergency”, or with cooperation, or with the legislative initiative. Habeas corpus lawsuits show us precarious conditions of imprisonment and excessive violation of human dignity; but if these measures were applied to hundreds of other cases that did not reach the courts, and were, in that short period of time, in about three hundred people, the sum of needless suffering is overwhelming.
Keywords: Fundamental rights; Constitution; Autonomous Region; Regional Government of the Azores; Illegal imprisonment; Covid-19